Family Ruptures and Intergenerational Transmission of Stress - Petra Persson; Maya Rossin-Slater (Research Institute of Industrial Economics (IFN), 2014)
The high and rapidly increasing prevalence of mental illnesses underscores the importance of understanding their causal origins. This paper analyzes one factor at a critical stage of human development: exposure to maternal stress from family ruptures during the fetal period. We find that in utero exposure to the death of a maternal close relative has lasting consequences on mental health in adulthood, as captured by 11 and 9 percent increases in the consumption of prescription drugs treating anxiety and depression, respectively, and a 23 percent increase in the average daily dose of medication for Attention Deficit Hyperactivity Disorder (ADHD).Further, children exposed prenatally to the death of a relative up to four generations apart are 20 percent more likely to be born low-birth-weight and 11 percent more likely to be hospitalized for conditions originating in the perinatal period in early childhood.Our results imply large welfare gains from preventing fetal exposure to severe stress; the decrease in consumption of prescription drugs treating depression alone can be valued at nearly 1 billion. More generally, our results point to in utero stress exposure as a potential cause of the rising incidence of several mental illnesses.
Keywords: I12; I14; I18; I31; J12; J13; 330; Mental health; Stress; Parental death; In utero; Depression; ADHD